EMI susceptibility of DTMOS opamps. Issue 2 (1st January 2013) - Richelli, A.
Abstract : The susceptibility to electromagnetic interference (EMI) of an amplifier based on dynamic threshold voltage MOS transistors (DTMOSs) has been analysed and improved thanks to an easy modification of the input differential stage. The final opamp has been designed in a 0.18μm standard CMOS process.